Primary angiosarcoma of the breast in a seventy-year-old female: a rare case report - Athar, Mohd; Singh, Siddharth; Chaudhary, Ashish Kumar; Sachan, Manjushree; Khan, Lubna; Jamal, Shahroz (Annals of Research Hospitals; Vol 1 (April 2017): Annals of Research Hospital, 2017)
Primary angiosarcoma (AS) of the breast is an extremely rare tumor. Radiological findings are non specific. Fine needle aspiration (FNA) yields a high false negative result so a tissue biopsy is mandated for a confirmed diagnosis. Surgical removal is the mainstay of the treatment. Role of adjuvant chemo radio therapy is debatable. Prognosis is usually poor. We report a case of a seventy years old lady presenting with a huge left breast mass. Sonomammography revealed a thick walled cystic mass filled with turbid fluid in left breast. FNA from elsewhere was reported as ductal carcinoma. As the patient presented to us, we confirmed the mass as AS on trucut biopsy. The patient was treated with WLE following which she was referred for adjuvant radiotherapy. Follow up on second postoperative month was uneventful.